(untitled) (مجلة إحالات, 2026)
The poetic language came as a reaction to the normative language of utilitarianism with strict boundaries and laws. The modern fiction is based on a revision of the linguistic system of writing through the creation of experimental creative spaces that were never consumed. , While the poetic language gives us a wide range of semantic options, and this makes the text open to various interpretations that nourish and develop the text, and the place is only an essential element in this discourse which is not founded without it. This is why the novelist tried to adapt it aesthetically to keep up with the expectations of the sinful reader